2012
DOI: 10.1371/journal.pone.0038799
|View full text |Cite|
|
Sign up to set email alerts
|

A Probabilistic Fragment-Based Protein Structure Prediction Algorithm

Abstract: Conformational sampling is one of the bottlenecks in fragment-based protein structure prediction approaches. They generally start with a coarse-grained optimization where mainchain atoms and centroids of side chains are considered, followed by a fine-grained optimization with an all-atom representation of proteins. It is during this coarse-grained phase that fragment-based methods sample intensely the conformational space. If the native-like region is sampled more, the accuracy of the final all-atom prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…In our previous communication, we presented which focused on enrichment of the near-native structures at a coarse-grained level. We have demonstrated that the improved coarse-grained models can lead to better all-atom models by refining the top quality coarse-grained models into all-atom models [18]. However, the question of how top quality coarse-grained models are identified was not addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous communication, we presented which focused on enrichment of the near-native structures at a coarse-grained level. We have demonstrated that the improved coarse-grained models can lead to better all-atom models by refining the top quality coarse-grained models into all-atom models [18]. However, the question of how top quality coarse-grained models are identified was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Models generated at a given iteration are stored in the final set and are not reused for subsequent iterations. inherits its sampling engine from [18]. The sampling is performed using an alternation of simulated annealing [21] and iterated hill climbing [22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-based methods using atomistic models have been used for fitting structures to low-resolution data, 2226 refining moderate to high-resolution X-ray data, 2729 providing low-to-moderate resolution models for use in crystal structure refinements, 30,31 folding some small proteins in MD simulations, 32 and docking macromolecules. 4 However, the success rate and accuracy of these and other applications of physics-based methods to macromolecular prediction problems remain substantially less than 100% (e.g.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…[4] Since the empirically derived energies used in these methods contain significant errors, the model with the lowest energy may not be the closest to the native structure. Typically, a small pool of models with the lowest energies are retained and analyzed for the identification of the best model.…”
Section: Introductionmentioning
confidence: 99%